The degree Availability of Social Responsibility at Class Teacherin faculty of Education of Damascus University " Field study for registration in the degree in the doctorate" - Jworea, Rehab (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research try to measure the degree Availability of Social Responsibility at Class Teacher in faculty of Education of Damascus University and the different according to variables of Class Teacher as (six, residence). The research problem poses questions about application these Methods. The sample included (326) students in the academic year 2017-2016.The research used questionnaire derived form the Social Responsibility Scale. The following statistical methods were used: frequencies, percent, means, standard deviations, t – test, and Pearson Correlation. Validity of the questionnaire was established though a jury of (7) of the teaching staff. Pilot sample consisted of (50) students. Reliability was established by Cronbach – Alpha Reliability atlest (0.901). The results showed that the degree of using social responsibility was high degree of Phrase which point out Moral and Self responsibility, and with middle degree of national responsibility, also in low degree of collectivism responsibility. In fact, there are statistically significant differences according to six in favor of female, and no differences according to residence.